Determinación del contenido de compuestos fenólicos y actividad inhibitoria de extractos de Artocarpus altilis (parkinson) Fosberg y Calathea allouia (aubl.) Lindl. sobre α-glucosidasa - Romero Rodríguez, María Del Carmen (2024)
The present study aimed to determine the phenolic compounds and inhibitory activity of ethanolic extracts of Artocarpus altilis (Parkinson) Fosberg (pandisho) and Calathea allouia (Aubl.) Lindl. (dale dale) about α-glucosidase. Samples were collected for convenience, oven-dried, and then micropulverized. Phenolic compounds were quantified using the UV/visible spectrophotometric technique, while the inhibitory activity was from alcoholic extracts at 100, 250, 500 and 1000 µg/mL in reaction mixture on α-glucosidase. The results show that most of the phenolic compounds are present in the leaves of A. altilis with 16278.46 mg/100g of total phenols; 47,987 mg/100g of flavonoids; 13,412 mg/100g of anthocyanins; but, C. allouia (Aubl.) Lindl – tuber obtained 0.007 mg/100g of catechins. In the inhibitory activity, an IC50=887.77 µg was obtained for the A. altilis leaf extract, while the A. altilis bark and C. allouia tuber extracts achieved IC50 > 1000 µg, allowing us to conclude that only the A. altilis leaves are considered active.